(untitled) (Indian Journal of Arid Horticulture, 2025)
Chilli (Capsicum ammm L) is one oflhc mos1 impor1an1 vegcwblc crops of the co1.1111ry ;lnd used as a spicc. The development of the tlgriculture primarily depends on the application of the scicnci; and technology by making tht.: bi;:st use of available resources. One of the major constraims of traditional chilli farming is low productivity due to non adoption of n::commcnded impi:ovc:d production Ledmologies. To overC(n:ne 1Ju:se constrainLS. K.VK-Paochmahals Wf1S conducted Front Line Demonstrations at various farmers fields to show the difference between improved production lechnology and c.xisting technology. During d,e study period, it was observed that in front line demonstrations, d1e improved Chim varie1y Gujarat Vegelable ChilJi-12 l rec